2016
DOI: 10.1111/pace.12961
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Sedation Reduces Lab Time Compared to General Anesthesia during Cryoballoon Ablation for AF Without Compromising Safety or Long‐Term Efficacy

Abstract: Compared to GA, MS during CBA for pAF was independently associated with shorter total EP laboratory time without compromising FFAF or complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 19 publications
1
20
0
2
Order By: Relevance
“…EAM, electroanatomical mapping associated complications and arrhythmia recurrence [9,14]. For the single-shot cryoballoon technique, immobilization is less essential and no differences in arrhythmia recurrence or complication rates were found comparing moderate sedation and general anesthesia [3,6]. Common cardiovascular risk factors and associated diseases such as obesity, smoking, sleep apnea or chronic obstructive lung disease (COPD) affect the respiratory system and could affect sedation [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EAM, electroanatomical mapping associated complications and arrhythmia recurrence [9,14]. For the single-shot cryoballoon technique, immobilization is less essential and no differences in arrhythmia recurrence or complication rates were found comparing moderate sedation and general anesthesia [3,6]. Common cardiovascular risk factors and associated diseases such as obesity, smoking, sleep apnea or chronic obstructive lung disease (COPD) affect the respiratory system and could affect sedation [15].…”
Section: Discussionmentioning
confidence: 99%
“…macroreentrant, microreentrant or focal atrial tachycardia, require electroanatomical mapping and therefore generally are treated by 3D-mapping guided point-by-point radiofrequency catheter ablation [1]. Most electrophysiological procedures can be performed under conscious moderate to deep sedation [4][5][6]. Immobilization of patients during long-lasting procedures is required to avoid complications by patients' unexpected bodily motion [7].…”
Section: Introductionmentioning
confidence: 99%
“…Prior work by our group and others has demonstrated cryoballoon ablation (CBA) for pulmonary vein isolation (PVI) to be associated with shorter procedure time, comparable clinical success rates, 4‐8 and significantly less pain 1,9 than radiofrequency ablation. CBA may be performed using moderate sedation (MS) rather than general anesthesia (GA) in patients who do not have a high‐risk airway or other medical indication for GA. MS avoids the risks associated with endotracheal intubation and the additional monitoring often required, as well as reduces total electrophysiology (EP) lab utilization time without compromising freedom from AF 10 . However, data comparing patient comfort and satisfaction between sedation modalities in CBA are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, a moderate sedation reduced laboratory time compared to GA (280.4 ± 54.1 min vs 245.5 ± 54.7 min, P<0.001) (ref. 7 ). In a study with remote magnetic ablation, Bun et al concluded that GA is not superior to local anesthesia (237 ± 50 min vs. 240 ± 61 min, P=0.84) (ref.…”
Section: Discussionmentioning
confidence: 99%